The 160 bp Insertion in the Promoter of Rht-B1i Plays a Vital Role in Increasing Wheat Height - Lou, Xueyuan; Li, Xin; Li, Aixia; Pu, Mingyu; Shoaib, Muhammad; Liu, Dongcheng; Sun, Jiazhu; Zhang, Aimin; Yang, Wenlong (Frontiers in Plant Science, 2016)
The extensive use of two alleles (Rht-B1b and Rht-D1b) at the Rht-1 locus in wheat allowed dramatic increases in yields, triggering the so-called “Green Revolution.” Here, we found that a new natural allelic variation (Rht-B1i) containing a single missense SNP (A614G) in the coding region significantly increased plant height against the genetic background of both Rht-D1a (11.68%) and Rht-D1b (7.89%). To elucidate the molecular mechanism of Rht-B1i, we investigated the promoter region. Sequence analysis showed that the Rht-B1i promoter could be divided into two classes depending on the presence or absence of a specific 160 bp insertion: Rht-B1i-1 (with the 160 bp insertion) and Rht-B1i-2 (without the 160 bp insertion). The promoter of Rht-B1i-1 contained 32 more possible cis-acting elements than Rht-B1a, including a unique auxin response element AUXREPSIAA4. Quantitative RT-PCR analysis indicated that the 160 bp insertion is likely to promote the transcription of the Rht-B1i-1 gene. The coleoptile lengths of wheat varieties treated with IAA, GA3, and IAA/GA3, combined with the histochemical staining of transgenic Arabidopsis containing the Rht-B1i-1 promoter, showed that the height-increasing effect of Rht-B1i-1 may be due to the synergistic action of IAA and GA3. These results augment our understanding of the regulatory mechanisms of Rht-1 in wheat and provide new genetic resources for wheat improvement.